Dynamics of Poverty in Indonesia: Political Economic Analysis - Lestari, Dwi Puji; Febrianti, Abida Nahar; Nurmutaqin, Erlita Amalia; Munandar, Moh. Aris; Uddin, Hafiz Rafi (International Journal of Sustainability in Research, 2024)
Poverty is a social phenomenon caused by economic factors. Poverty is the economic inability to meet basic food and non-food needs. One of the things that can determine and measure poverty is expenditure. For a long time, poverty has been a major problem in Indonesia. The incidence of poverty increased by more than a third during the crisis compared to the pre-crisis period. Meanwhile, Indonesia has experienced significant social and political changes along with increased democracy, decentralization of government, and increased transparency compared to the past. But poverty levels remain high based on various factors. This article concentrates on the problem of poverty which continues to increase even though many poverty alleviation programs have been created by the government.